Integrated design and PLM applications in aeronautics product development - van Wijk, D.; Eynard, B.; Troussier, N.; Belkadi, F.; Roucoules, L.; Ducellier, G. (Cranfield University Press, 2009)
Well known challenges in Aeronautic industry, namely reducing time to market, risks and development costs, could be reached thanks to innovative design methods supported by PLM technologies. Such methods are based on integrated design or collaborative engineering enabling close exchanges and cooperation between the project partners. The paper proposes a survey on integrated design methods and PLM technologies. It presents the development of a collaborative design platform, as part of SEINE project, which aims to improve partners’ cooperation in the French aeronautics supply chain. The paper also discusses how to include multiple expertises and integrated design in this collaborative platform.
Organised by: Cranfield University
Keywords: Collaborative Engineering; Integrated Design; Data Exchange; PLM; Aeronautics Industry